N2O production by mussels: Quantifying rates and pathways in current and future climate settings - Voet, Helena; Soetaert, Karline; Moens, Tom; Bodé, Samuel; Boeckx, Pascal; Van Colen, Carl; Vanaverbeke, Jan (Frontiers in Marine Science, 2023)
Blue mussels (Mytilus edulis) are an abundant and economically important species across the North Sea. Partly because of their potent filter feeding and associated shell biofilm, they are able to influence and alter the surrounding marine ecosystem. As a result of proliferating offshore wind farms (OWFs), whose turbine foundations are rapidly colonised by suspension feeding artificial hard substrate communities dominated by M. edulis, as well as planned co-location strategies of these OWFs with mussel mariculture, their numbers will only increase towards the future. On top of these local stressors, global climate change is exerting additional pressure on the marine environment. This study focusses on the link between M. edulis, its microbial shell biofilm and the local nitrogen cycling by quantifying the magnitude and underlying pathways of mussel-associated nitrous oxide (N2O) production. A set of closed-core incubations established nitrifier denitrification as the main chemical pathway of M. edulis related N2O production, although ammonium, nitrite and nitrate all acted as possible precursors. Additional future-climate experiments revealed that blue mussel’s total N2O production, as well as its metabolic activity and the relative contribution of its shell biofilm, were affected by warming (+ 3°C), acidification (- 0.3 pH units), or the combination of both. Because the effects of temperature and acidity were often of an antagonistic nature, the results suggest a relatively small net effect on local N2O production in future-climate marine environments. However, N2O production rates were several orders of magnitude lower than other measured N species (NH4+, NO2− and NO3-), making substantial mussel-associated N2 production likely. This would greatly affect the local eutrophication levels or even bioavailable nitrogen concentrations.